2013
DOI: 10.1051/mmnp/20138503
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Traveling Waves in Partly Parabolic Systems

Abstract: Abstract. We review recent results on stability of traveling waves in partly parabolic reactiondiffusion systems with stable or marginally stable equilibria. We explain how attention to what are apparently mathematical technicalities has led to theorems that allow one to convert spectral calculations, which are used in the sciences and engineering to study stability of a wave, into detailed, theoretically-based information about the behavior of perturbations of the wave.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…This wave represents a combustion front that leaves behind of it high temperature u − = 1/β and no fuel, while in front of it temperature is 0 and there is fuel, with concentration normalized to 1. As discussed in Paragraph 3.2 of [GLS3], Hypothesis 2.10 is true and Hypothesis 2.4 can be verified (partly numerically) for small β > 0.…”
Section: Stable Manifoldsmentioning
confidence: 70%
See 2 more Smart Citations
“…This wave represents a combustion front that leaves behind of it high temperature u − = 1/β and no fuel, while in front of it temperature is 0 and there is fuel, with concentration normalized to 1. As discussed in Paragraph 3.2 of [GLS3], Hypothesis 2.10 is true and Hypothesis 2.4 can be verified (partly numerically) for small β > 0.…”
Section: Stable Manifoldsmentioning
confidence: 70%
“…In this system, u is the temperature, v is the concentration of unburned fuel, g is the unit reaction rate, and β > 0 is a constant parameter. This system was a primary guiding example in [G,GLS1,GLSS,GLS2,GLS3]. One motivation for looking at this well-studied problem, in which the reactant does not diffuse, was heat-enhanced methods of oil recovery in which the reactant is coke contained in the rock formation, see [AY].…”
Section: Stable Manifoldsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the analysis on a calcium model (CKKONS model [2,19]), which is based on current theory for waves of intracellular calcium concentration, indicates that the structure of one-dimensional waves in this model is quite different from that of the FHN system. Further, the stability analysis of waves in the CKKONS model is more subtle than those for the FHN system (see [19,6]). Motivated by these previous works, one may expect that the theory of two-dimensional waves in the CKKONS model is different from that in the FHN system.…”
Section: Introductionmentioning
confidence: 99%
“…We remark that most analytical works on Goldbeter's model are only for the reduced system which is a piecewise linear approximation to Goldbeter's model, and which is a phenomenological formulation, and so, does not involve many biological details.Recently, the analysis on a calcium model (CKKONS model [2,19]), which is based on current theory for waves of intracellular calcium concentration, indicates that the structure of one-dimensional waves in this model is quite different from that of the FHN system. Further, the stability analysis of waves in the CKKONS model is more subtle than those for the FHN system (see [19,6]). Motivated by these previous works, one may expect that the theory of two-dimensional waves in the CKKONS model is different from that in the FHN system.Previous studies [10,12,22,20] have demonstrated that the curvature relation of waves is crucial for the evolution of waves in two spatial dimensions.…”
mentioning
confidence: 99%